Justifying Fiduciary Duties - Miller, Paul (McGill Law Journal / Revue de droit de McGill, 2013)
Fiduciary duties are critical to the integrity of a remarkable variety of relationships, including those between trustee and beneficiary, director and corporation, agent and principal, lawyer and client, doctor and patient, parent and child, and guardian and ward. Notwithstanding their variety, all fiduciary relationships are presumed to enjoy common characteristics and to attract a core set of demanding legal duties, most notably a duty of loyalty. Surprisingly, however, the justification for fiduciary duties is an enigma in private law theory. It is unclear what makes a relationship fiduciary and why fiduciary relationships attract fiduciary duties. This article takes up the enigma. It assesses leading reductivist and instrumentalist analyses of the justification for fiduciary duties. Finding them wanting, it offers an alternative account of the juridical justification for fiduciary duties. The author contends that the fiduciary relationship is a distinctive kind of legal relationship in which one person (the fiduciary) exercises power over practical interests of another (the beneficiary). Fiduciary power is a form of authority derived from the legal capacity of the beneficiary or a benefactor. The duty of loyalty is justified on the basis that it secures the exclusivity of the beneficiary’s claim over fiduciary power so understood.